Research on the Hole Length Ratio of Fan-Shaped Holes in Flat Plate Film Cooling - Zhou, Xun; Qin, Runxuan; Cai, Le (Frontiers in Energy Research, 2021)
To study the influence of different hole length ratios on the flow structure and film cooling efficiency, a calculation model of fan-shaped hole was constructed and numerically studied. The effect of different hole length ratios on the cooling efficiency under different blowing ratios was compared and analyzed. The results showed that as the blowing ratio increases, the overall average efficiency of most of the hole length ratio cases first increases and then decreases. Only in the case with a cylindrical part length/total length ratio of 0.5 did the efficiency continue to increase. When the blowing ratio is small, the spanwise average efficiency of each hole length ratio case is closer, but the flow structure and efficiency distribution are quite different. For the medium blowing ratio, the overall average efficiency of the small hole length ratio case is higher, and the efficiency decreases as the hole length ratio increases. When the cylindrical part length/total length ratio is further increased to 1, the cooling efficiency region basically converges into a spanwise narrow region. For larger blowing ratio conditions, after 10D after the hole outlet, the case with a cylindrical part length/total length of 0.5 is more efficient.